EFFECT OF CONCENTRATIONS AND DOSE ON ATTRACTION AND REPELLENT PERCENTAGE OF WATER EXTRACTS OF SOME PLANTS IN LARVAE OF Plodia interpunctella (Hubn.) - Nazar M. Al- Mallah (Mesopotamia Journal of Agriculture)
The results of studying the effect of 1. 4. 7 and 9 % concentrations and 0.1 . 0.3 mL dose of water extracts of Myrtus communis L. Ruta graveolens and Mentha piperita L. on mortality. attraction and repellent to larvae of Plodia interpunctella (Hubn.). showed a different variation in mortality. attraction and repellent percentage to the larvae according to the kind of extracts. concentrations and doses. The concentration 9 % of R. graveolens showed a highest mean mortality reached 74 %. and the relative toxicity reached 0.63 . 0.71 and 1.0 for M. communis . R. graveolens and M. piperita respectively and the relative efficieny values reched 157.44% for R. graveolens. 100% for M. communis and 132.14% for M. piperita. The results also revealed that the highest mean of attraction reached 46.67 by M. piperita at 1% concentration and 0.1 ml dose one hour after treatment followed by M. communis extracts which reached 46.67% at 9% concentration and 0.1 ml one hour after treatment. the M. piperita extracts produce a supreme repllent effect reached 36.67% at 9% concentration and 0.1 ml Dose one hour after treatment statistical analysis results showed a significant variation in balance values according to the extract concentrations. doses and time from treatment.